A Descriptive Analysis of College Students’ Experiences of Female-Perpetrated Sexual Assault - Gambardella, Gianna (Journal of contemporary criminal justice, 2020)
The current study sought to explore the experiences of college students who have experienced female-perpetrated sexual assault, and to compare their experiences to those of students assaulted by male perpetrators. A total of 11,165 college students across 11 years completed an online, anonymous survey measuring self-reports of sexual violence, context surrounding their victimization, help-seeking, and well-being. Of the students surveyed, 531 students reported experiencing sexual assault and identified both their own gender and the gender of their perpetrator, and 14% reported having experienced female-perpetrated sexual assault. Victims of female perpetrators were more likely to report their perpetrator being an (ex)intimate partner and less likely to be a stranger. Victims of female perpetrators were also more likely to report that their victimization involved their own drug use. Overall, victims of female-perpetrated sexual assault were less likely to tell anyone about their victimization, or to report to on- or off-campus resources. Finally, our findings suggest that victims of female perpetrators have comparable well-being to victims of male perpetrators. These finding contribute to the overall understanding of female-perpetrated sexual assault.